RESEPSI AL-QUR’AN DI MEDIA SOSIAL: STUDI KASUS FILM ANIMASI NUSSA EPISODE “HIII SEREM!!!” - A'yun, Qurrata (UIN Sunan Kalijaga Yogyakarta, 2020)
This article examines the Qur'anic reception on social media, especially in one episode of the Nussa animated film